ObServe: Software for collecting data from observations at sea for longline and purse seine fisheries - Cauquil, Pascal; Ob7 team (Zenodo, 2022)
Observation data collected aboard fishing vessels are essential to describe the impact of fisheries on fish community and is captures is one of the pillar of the Ecosystem Approach to Fisheries (EAF). Data on whether fish are caught, when, where and how, inform a wide variety of tasks for fishery management. Such data are particularly useful to assess the state of targeted species as well as those that are accidentally caught. Many fish stocks are being exploited close to their maximum sustainable yield (MSY) and plenty of other stocks are over-exploited, needing therefore a cautious monitoring of their recovery. The French National Research Institute for Sustainable Development [1] (IRD, France) has been sending observers aboard tropical purse-seiners since 1995 in the Atlantic and Indian Oceans, and longliners since 2007 in the Indian Ocean, to conduct scientific observations aboard French vessels to monitor tropical fisheries for his own research then in the framework of EU Data Collection Framework [2] (DCF), set out in Regulation (EU) 2017/1004 and a multiannual programme (EU MAP). To monitor this program, the Exploited Tropical Pelagic Ecosystems Observatory [3] (ex-Observatoire Thonier) from IRD has been developing since 2010 an information system named ObServe that is intended to manage data collected. ObServe consists of (i) a central database based on PostgreSQL, (ii) a Java-based software used for data acquisition and management, and (iii) data synchronization features between these two modules. This system was originally dedicated to purse-seine fisheries but supports longline also. ObServe was designed to be generic in order to cover the needs of any observation program of purse-seine or longline fisheries. ObServe is being used by several institutes, administration and companies that carry out observer surveys on purse seiners: IEO [4] and AZTI [5] (Spain), SFA [6] (Seychelles), BVLR [7] (France), AMEXPERT [8] (Ivory Coast), Terres Australes et Antarctiques Françaises [9] (France), and longliners: ...